2008
DOI: 10.1007/s00425-008-0783-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of severe water stress on linear and cyclic electron fluxes through Photosystem I in spinach leaf discs in CO2-enriched air

Abstract: Linear and cyclic electron fluxes through Photosystem I in 1% CO(2) were quantified in spinach leaf tissue under severe water stress. Using actinic light with a peak at 697 nm for preferential light absorption by Photosystem I while also stimulating Photosystem II to improve redox poising, the cyclic electron flux after 60 s of illumination was a substantial proportion (33-44%) of the total electron flux through PSI at irradiances up to ~1,070 micromol photons m(-2) s(-1). At the maximum irradiance, the cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 37 publications
4
30
1
Order By: Relevance
“…By contrast, introducing the crr2-2 mutation into hcef1 (hcef1 crr2-2, Figure 6B) resulted in severely hindered photosynthesis, suggesting that hcef1 imposes a requirement for additional ATP that is fulfilled via CEF1 that involves NDH. Similar increases in CEF1, presumably reflecting increased chloroplast ATP demand, have been reported upon imposing environmental stresses, such as drought (Jia et al, 2008;Kohzuma et al, 2008). At least in the case of hcef1, alternative ATP/NADPH balancing mechanisms (e.g., water-water cycle [Asada, 2000] and the malate shunt [Scheibe, 2004]) were apparently unable to compensate for the loss of CEF1 upon mutation of NDH.…”
Section: Cef1 Involving Ndh Appears To Be Critical For Maintaining Thmentioning
confidence: 76%
See 1 more Smart Citation
“…By contrast, introducing the crr2-2 mutation into hcef1 (hcef1 crr2-2, Figure 6B) resulted in severely hindered photosynthesis, suggesting that hcef1 imposes a requirement for additional ATP that is fulfilled via CEF1 that involves NDH. Similar increases in CEF1, presumably reflecting increased chloroplast ATP demand, have been reported upon imposing environmental stresses, such as drought (Jia et al, 2008;Kohzuma et al, 2008). At least in the case of hcef1, alternative ATP/NADPH balancing mechanisms (e.g., water-water cycle [Asada, 2000] and the malate shunt [Scheibe, 2004]) were apparently unable to compensate for the loss of CEF1 upon mutation of NDH.…”
Section: Cef1 Involving Ndh Appears To Be Critical For Maintaining Thmentioning
confidence: 76%
“…Some groups have reported substantial increases in CEF1 under environmental stress, such as drought (Jia et al, 2008;Kohzuma et al, 2008) or high light (Baker and Ort, 1992), or during the induction of photosynthesis from prolonged dark acclimation (Joë t et al, 2002;Joliot and Joliot, 2002). Others have found only small contributions of CEF1 to the photosynthetic energy budget, especially under steady state conditions Harbinson et al, 1989;Avenson et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, the decreased amount of NADP + causes the activation of pgr5-dependent CEF (Okegawa et al, 2008). CEF has also been demonstrated to be accelerated in stress conditions, such as strong light (Clarke and Johnson, 2001;Miyake et al, 2004;DalCorso et al, 2008), low CO 2 (Munekage et al, 2002), and drought (Golding and Johnson, 2003;Golding et al, 2004), although not in drought when the air is enriched in CO 2 and the redox posing for CEF is near optimal (Jia et al, 2008). Our results demonstrated that CEF generates an acidic lumen and a DpH and helps avoid photoinhibition by preventing photodamage to PSII in a qE-independent manner and minimizing inhibition of the repair of photodamaged PSII in a qE-dependent manner.…”
Section: Cef Reduces Inhibition Of Protein Synthesis-dependent Repairmentioning
confidence: 99%
“…The decomposition of the kinetic curve of P700 + dark reduction into sev eral exponential terms provides the means to compare the rates of electron fluxes to P700 + along the cyclic route and from alternative sources [13][14][15]. Another approach to CET quantification makes use of the leaf exposure to white light (WL) under control conditions and in the presence of methyl viologen (MV), an agent that effectively consumes all electrons available on the acceptor side of PSI, thus excluding CET [15,16].…”
Section: Introductionmentioning
confidence: 99%